Development of Self-emulsified Nanoemulsion of Telmisartan by Lowenergy Method Using D Optimal Mixture Matrix Design Approach as a Tool for Optimization Methodology - Jadhav, Sarika R. (Asian Journal of Pharmaceutics (AJP), 2025)
Introduction: Telmisartan is one of the promising, long-lasting antihypertensive agents that act as an angiotensin II receptor blocker. It belongs to biopharmaceutics classification system (BCS) class II having low water solubility and very low oral bioavailability. Materials and Methods: The objective of the study is to design and develop self-emulsified nanoemulsion (SNEDDS) of telmisartan by low-energy method using a factorial design approach as a tool for optimization methodology. The solubility of the drug in different oils, surfactants, and cosurfactants was analyzed. Pseudo-ternary phase diagram was used to identify the self-nanoemulsifying region along with the optimized concentration of oil, surfactant, and cosurfactant. D-optimal mixture matrix design approach was applied to selected elements to find out the optimized batch. A total of 16 batches were analyzed for particle size, drug content zeta potential along with other physiochemical characteristics. Results: Telmisartan SNEDDS was developed using oleic acid as oil (15%), tween 20 (surfactant): Transcutol P (cosurfactant) (3:1 ratio) (70%) as nanoemulsion system components. D-optimal mixture matrix design was used to find out different possible batches having an optimal blend of mixture components. From the various combinations optimized batch was further evaluated for different physicochemical properties and found within acceptable range. The droplet size of the selected optimized nanoemulsion was within 200–250 nm, polydispersity index 0.240, zeta potential -40.6 mV, determined using a particle size analyzer. Conclusion: The solubility of poorly water-soluble telmisartan had improved with a selfanoemulsifed nanoemulsion drug delivery system. Oleic acid as oil (15%), tween 20 (surfactant): Transcutol P (cosurfactant) (3:1 ratio) (70%) found to be compatible and suitable for formation of stable nanoemulsion system. Using D-optimal mixture matrix design approach and applying the low energy method telmisartan-containing nanoemulsions were prepared. The optimized formulation showed the improved drug content and drug released as compared to the plain drug. The developed optimized formulation with design experts gives promising strategies to improve the efficacy and effectiveness of poorly soluble drugs such as telmisartan.